LIBERDADE DE IMPRENSA E EXPRESSÃO: DIGITAL, POLÀTICA E CIVIL (CIPEEX, 2022)
THE PRESENT RESEARCH CONSIDERS AND SEEKS QUESTIONS RELATED TO FREEDOM OFEXPRESSION, WITH DIGITAL, POLITICAL AND CIVIL BIAS, WITH THIS, A QUALITATIVE METHODOLOGYWAS USED, WITH LITERATURE REVIEW, THUS, THE DELIMITATION OF THESE TWO.